A Study in Code Mixing and Code Switching on Podcast of Millennial Power Channel - Nurfitriani (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2022)
The adjective of the research were to find out the types of code mixing and code switching.This research focuses in analysis DyahRoroEsti’s utterances in Podcast where the channel is “Millennial Power” which contained code mixing and code switching in the audio as the data of research. This research used Qualitative Content AnalysisDesign. The technique of data analysis used theory of Miles and Huberman that contains data reduction, data display and conclusion drawing. The result of this research found that there are three types of code mixing and code switching. Code mixing contained insertion which occured 31 data, alternation 8 data and congruent lexicalization 1 data. Code switching contained tag switching which occured 5 data, intra-sentential switching 43 data and inter-sentential switching 22 data. It was expected that this research helps everyone who wants to know about bilingualism and code mixing and code switching.